CRITICAL ANALYSIS ABOUT THE PROPOSAL FOR REPEAL OF LAW No. 12.318/2010 (BILL No. 6371/2019) - Thomas Gubert, William (Revista Gênero e Interdisciplinaridade, 2023)
This review article proposes to examine the justifications elaborated by the Bill (PL) nº. 6371/2019 in the light of doctrine and contemporary critical reflections. To this end, the specific comments made by Federal Deputy Iracema Portella are analyzed and with the support of several jurists (revised literature) in the highlighted points, the conclusion was reached to maintain - within the homeland Legal Order - of the Parental Alienation Law (non-repeal of Law Nº. 12,318/2010); observed the optimization and the quantitative and qualitative intensification of the expertise to the decision and the case-by-case verification.